Industria semillera en el Paraguay: en el contexto de la tasa tecnológica - González, Dólia Melania Garcete (2013)
The soybean Glycine max. (L.) Merrill is a very important item for Paraguay, which ranks the country among the world's sixth largest producer. It is a crop with higher production area in Paraguay, for its great economic return for producers. In the past three years the average increase in surface area was about 6% environment, while the average increase in productivity was 13%, which implies that the incorporation of edge germplasm and crop management through technological tools available in the market, have proven positive effect on soybean production at national and regional levels. Other major factors which have been found a significant improvement in the national productive sector is the implementation of private agreements for recognition by the use of biotech events, the same could not be positive effect on the use of germplasm although means for accessing main events are to biotechnology therethrough. This work will seek to assess all situations regarding capture systems either by the use of biotechnology, or the use of germplasm, as well as discuss the benefits of the agreement in Paraguay and the results of the application of those funds. The AMBA signed in Paraguay is highly successful in the soy production chain; with the soybean seed system by charging the beneficiary of the technology fee, these resources also allows all participants an intense economic activity.